Pulmonary arteriovenous malformation (PAVM) and pregnancy - Gulnar Murzabekova; Gulnar Mustafinova; Arlan Rakhatayev; Kamila Kalieva; Kamila Dzheksenbieva (National Scientific Medical Center, 2017)
Pulmonary arteriovenous malformation is very rare anomaly of the lung; the estimated incidence is thought to be around 2-3 per 100 thousand. Occurrence of this pathology in pregnant women has not been previously described in the literature.